New-onset atrial fibrillation in critically ill patients and its association with mortality: A report from the FROG-ICU study. (1st September 2018) - Arrigo, Mattia; Ishihara, Shiro; Feliot, Elodie; Rudiger, Alain; Deye, Nicolas; Cariou, Alain; Guidet, Bertrand; Jaber, Samir; Leone, Marc; Resche-Rigon, Matthieu; Vieillard Baron, Antoine; Legrand, Matthieu; et al.
Abstract: Background: Atrial fibrillation (AFib) is associated with adverse outcome in critical illness, but whether this effect is independent from other risk factors remains uncertain. New-onset AFib during critical illness may be independently associated with increased in-hospital and long-term risk of death. Methods: FROG-ICU was a prospective, observational, multi-centre cohort study designed to investigate the outcome of critically ill patients. Inclusion criteria were invasive mechanical ventilation and/or treatment with a positive inotropic agent for >24 h. Heart rhythm was assessed at inclusion and during ICU stay with digital ECG recordings. Among patients who had AFib during ICU stay, new-onset and recurrent AFib were diagnosed in patients without and with previous history of AFib, respectively. Primary endpoint was in-hospital mortality; secondary endpoint was 1-year mortality among ICU survivors. Results: The study included 1841 critically ill patients. During ICU stay, AFib occurred in 343 patients (19%). New-onset AFib (n = 212) had higher in-hospital mortality compared to no AFib (47 vs. 23%, P  < 0.001) or recurrent AFib (34%, P  = 0.032). New-onset AFib showed increased risk of in-hospital death after multivariable adjustment compared to no AFib (OR 1.6, P  = 0.003) or recurrent AFib (OR 1.8, P  = 0.02). Among the 1464 ICU-survivors, new-onset AFib during ICU stay showed higher post-ICU risk of death compared to no AFib (HR 2.2, P  < 0.001). After multivariable adjustment, new-onset AFib showed higher post-ICU risk of death compared to no AFib (HR 1.6, P  = 0.03). Conclusion: New-onset AFib is independently associated with in-hospital and post-ICU risk of death in critically ill patients. Highlights: FROG-ICU was a multi-centre cohort study investigating outcome of critically ill patients. During ICU stay, AFib occurred in 19% of patients New-onset AFib, is independently associated with increased risk of in-hospital death. New-onset AFib during critical illness, is independently associated with one-year outcome of ICU survivors.